2014
DOI: 10.3390/ijms15058509
|View full text |Cite
|
Sign up to set email alerts
|

Lyophilized Platelet-Rich Fibrin (PRF) Promotes Craniofacial Bone Regeneration through Runx2

Abstract: Freeze-drying is an effective means to control scaffold pore size and preserve its composition. The purpose of the present study was to determine the applicability of lyophilized Platelet-rich fibrin (LPRF) as a scaffold for craniofacial tissue regeneration and to compare its biological effects with commonly used fresh Platelet-rich fibrin (PRF). LPRF caused a 4.8-fold ± 0.4-fold elevation in Runt-related transcription factor 2 (Runx2) expression in alveolar bone cells, compared to a 3.6-fold ± 0.2-fold increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 37 publications
5
71
1
4
Order By: Relevance
“…The expression of BSP-I increased gradually from Day 2 to Day 7. These results were in line with those of Li et al and Tu et al which posited that BSP-I expression constituted a late stage osteogenic differentiation marker [15,16]. The addition of PRF to GSC culture medium during osteogenic differentiation can stimulate BSP-I expression, a position adopted in the study by Duan et al that showed significantly increased BSP-I or Osteopontin expression in combined human GSC and PRF on Day 21 [10].…”
Section: Discussionsupporting
confidence: 88%
“…The expression of BSP-I increased gradually from Day 2 to Day 7. These results were in line with those of Li et al and Tu et al which posited that BSP-I expression constituted a late stage osteogenic differentiation marker [15,16]. The addition of PRF to GSC culture medium during osteogenic differentiation can stimulate BSP-I expression, a position adopted in the study by Duan et al that showed significantly increased BSP-I or Osteopontin expression in combined human GSC and PRF on Day 21 [10].…”
Section: Discussionsupporting
confidence: 88%
“…The ELISA test that was performed showed the potential release of growth factor (IGF-1) by L-PRF. The release of the growth factors was in a continuous manner up to 14 days, as reported in many published studies [27][28][29][30] . The composition of the fibrin network allows a slow but high-level of fibrillar aggregation in L-PRF, entrapping proteins and growth factors to the binding domains of fibrin molecules at the same time.…”
Section: Discussionmentioning
confidence: 59%
“…CGF was mechanically separated using scissors and then compressed into a thin membrane. Surface parameters such as topography and hardness markedly affect cell behavior and the release of growth factors (10,12,23). SEM analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%